Pengembangan Media Video Pembelajaran Pada Mata Kuliah Fotografi - Rifky Aditya; Zuliarni Zuliarni (Universitas Negeri Padang, 2022)
This study aims to produce video media products using Wondershare Filmora as a learning medium that is in accordance with the eligibility criteria for media and materials in photography courses. The research conducted is Research and Development (R&D) research. The product validity test was carried out by three validators, namely two media validators and one material validator. The product trial was carried out for students of the 2020 FIP UNP ID card affairs who were the subject of trials with a total of 20 people to find the feasibility of learning video media. Data collection instruments and tools used are documentation, material and media expert validation formats, assessment sheets and questionnaires. Based on the results of the feasibility assessment from material experts and media experts, namely, the results of material validation obtained a